Comparison of the effectiveness of various lettuce (Lactuca sativa L.) hybridization methods - M. V. Kovalchuk (Овощи России, 2024)
Relevance. Lettuce is a widespread green crop. The high demand for lettuce products, as well as for new varieties, drives the development of different breeding practices for this crop. It is the most promising to use hybridization method in the lettuce breeding for a diverse source material production. However, lettuce is a self-pollinating plant with small flowers and a short flowering period (about three hours), so the technique of castration and pollination is difficult. The current methods of lettuce hybridization vary in efficiency and labor intensity. This study aims to compare the effectiveness of three different hybridization methods and to obtain a source material for lettuce breeding using these methods.Materials and methods. 15 varieties of different variety types of lettuce were studied in various combinations. Three hybridization methods was conducted in the conditions of the Moscow region and the Krasnodar Territory: 1) using flies as pollinating insects, 2) using manual castration by cutting off the inflorescence of unopened buds with pollen inside and washing off pollen residues followed by manual pollination ("Clip and Wash" method), and 3) using manual emas- culation with a single pollen wash, also followed by manual pollination. The hybridity level assessment and the breeding material selection were performed according to the main morpho- logical and economically valuable characteristics.Results. In the period from 2021 to 2023, 529 hybrid plants were produced using three different hybridization methods of lettuce. Out of these, 150 plants of various variety types and forms were selected for further breeding. The "Clip and Wash" method was found to be the most effective in terms of achieving the highest hybridization percentage (92-100%) with less labor costs in organizing crosses. However, the hybridization process using insect pollination was less effective and required more labor, but it was also possible to pollinate a larger number of inflorescences using this method.